2022
DOI: 10.3390/app12157932
|View full text |Cite
|
Sign up to set email alerts
|

Damping Behavior of Hybrid Composite Structures by Aeronautical Technologies

Abstract: Hybrid composite laminates are manufactured by using technologies and raw materials of the aeronautic sector with the aim to improve the damping behavior of composite structures. Matrix hybridization was achieved by laminating carbon fiber reinforced (CFR) plies with elastomer interlayers. Up to 10 different composite sandwich architectures were investigated by changing the stacking sequence, the thickness of the elastomer layers, and the elastomer typology, whereas the total number of the CFR plies was fixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The synergetic effect of multiple reinforcements such as SiC/Al 2 O 3 in an Al matrix alters the porosity that causes the variation in the mechanical properties of Al metal matrix composites [23,24]. Recently, hybrid metal matrix composites have attracted attention for use in different applications and research has been carried out to understand the various properties that these hybrid composites have to offer [25][26][27][28][29][30][31]. Zhang et al (2020) [25] studied the evolution of the microstructure of two varieties of hybrid composites such as Al/SiC/graphite and Al/SiC/graphene by the PM process, where graphene in the Al and nanostructure composite could be formed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synergetic effect of multiple reinforcements such as SiC/Al 2 O 3 in an Al matrix alters the porosity that causes the variation in the mechanical properties of Al metal matrix composites [23,24]. Recently, hybrid metal matrix composites have attracted attention for use in different applications and research has been carried out to understand the various properties that these hybrid composites have to offer [25][26][27][28][29][30][31]. Zhang et al (2020) [25] studied the evolution of the microstructure of two varieties of hybrid composites such as Al/SiC/graphite and Al/SiC/graphene by the PM process, where graphene in the Al and nanostructure composite could be formed.…”
Section: Introductionmentioning
confidence: 99%
“…Manohar et al (2022) [29] investigated the microstructure and mechanical properties of Al7075/graphite/SiC hybrid composites; they found that 8 vol.% of graphite and 2 vol.% of SiC maximized the mechanical properties. Proitte et al (2022) [30] studied the damping behavior of a fiber composite in aeronautical technology. In addition to ceramic reinforcements, iron oxide (Fe 2 O 3 ) is also used to make hybrid composites [31].…”
Section: Introductionmentioning
confidence: 99%